Analisis Kualitas Pelayanan Dan Kepercayaan Terhadap Minat Beli Di Febi One Mart - Diana Fatikah; Indah Putri Setiani; Maylany Sukmawati; Nur Fahmi; Nurul Kusuma Astuti (Academica: Journal of Multidisciplinary Studies, 2022)
This study aims to examine the buying interest of students in Febi One Mart in terms of service quality and trust as independent variables. The subject of this research were students of UIN Raden Mas Said Surakarta who had made purchase transaction at Febi One Mart. The research data were obtained from the distribution of online questionnaires. The research data processing used multiple linear regression analysis on SPSS 23. The results showed that the service quality variable (X1) has a positive effect on buying interest with a t-count value of 6.947 and a significance value (sig) of 0.000. Trust variable (X2) has a positive effect on buying interest with a t-count value of 6.853 and a significance value (sig) of 0.000. Keywords: Service Quality, Trust, Buying Interest